PENGARUH KONSENTRASI NITROGEN DAN FOSFOR TERHADAP PERTUMBUHAN, KANDUNGAN PROTEIN, KARBOHIDRAT DAN FIKOSIANIN PADA KULTUR Spirulinafusiformis - Chrismadha, Tjandra; Panggabean, Lily M; Mardiati, Yayah (BERITA BIOLOGI, 2006)
An experiment was carried out to find out the optimum nitrogen and phosphorous concentration for growth and phycocyanin production in Spirulina fusiformis culture. The cultures were grown in Zarouk medium at various nitrogen and phosphorous concentrations, which were 0.0 mM N, 7.5 mM N, 15.0 mM N, 22.5 mM N, and 30.0 mM N, as well as 0 raM P, 90 mM P, 180 mM P, 270 mM P, and 360 mM P, with four replications each. The result shows that optimal growth of the alga, which is expressed in terms of the biomass yield, was achieved at nitrogen and phosphorous concentration of 7.5 mM and 270 mM, respectively.At the same time, the highest phycocyanin content was obtained at nitrogen concentration of 22.5 mM, which was 1,2% of the biomass, and phosphorous concentration of 360 mM, which was 1.1% of the biomass. According to this result, it is suggested the optimum concentration of nitrogen and phosphorous in the media of Spirulina culture for phycocyanin production is 22.5 mM and 360 mM, respectively.